Differences in compact bone tissue microscopic structure between adult humans (Homo sapiens) and Assam macaques (Macaca assamensis) - Korakot Nganvongpanit (2018)
© 2015 Elsevier Ireland Ltd. This study investigated the osteon structure of adult humans and Assam macaques, which served as a nonhuman primate model, to find an adequate key for species identification. Samples of compact bone from humans (n = 5) and Assam macaques (n = 5) - including humerus (n = 20), radius (n = 20), ulna (n = 20), femur (n = 20), tibia (n = 20) and fibula (n = 20) - were processed using conventional histological techniques. 100 secondary osteons from each sample were evaluated under light microscopy. Parameter measurements included: diameter, perimeter and area of Haversian canal and osteon; distance between centers of Haversian canals; and ratio between diameter of Haversian canal and osteon. Four parameters, including diameters and areas of Haversian canal and osteon, demonstrated significantly higher (P < 0.05) values in humans than in Assam macaques. Therefore, compact bone microstructure could thus be used as a potential tool to differentiate human and nonhuman primates.